Sekolah Perempuan Perkebunan Berbasis Potensi Alam Untuk Mengembangkan Life-Skill Masyarakat Desa Harjomulyo - (indonesia), Supeno; (indonesia), Alifiah Putri; (indonesia), Gloria Sagita Harimisa; (indonesia), Aisyah Emelia Ismawati; (indoensia), Zulfa Nishom Fahmi (JURNAL KASTARA, 2024)
Harjomulyo Village, located in Jember district, covers 38.44 km2 and is 700 meters above sea level. Given its geographical location, Harjomulyo has promise in the agricultural and plantation sectors, which is aided by the presence of wadung plantations that surround the majority of the communities. Despite this promise, the author believes that some issues, particularly those concerning education, life skills, and economics, require further discussion. Based on the problem identification, the remedy was bundled into the "Sekolah Perempuan Perkebunan" program. The purpose of this program is to create a platform for women in Harjomulyo Village to improve their reading ability, life skills, and capacity to manage and improve the quality of their families. The implementation process is separated into three stages: preparation and recognition of potential, challenges, and community needs; training and provision; and measurement and evaluation. The program's results include improved living skills such as making eco-prints, aromatherapy candles, and banana leaf purses. The initiative concludes with the establishment of a "Sekolah Perempuan Perkebunan," which will help Harjomulyo Village residents enhance their life skills.